Improving Congnitive Skills Through Loose Part Media in Group B of the Principal State Kindergarten of Waisai, Raja Ampat District - Dewi Murniasih; Nursalim; Ismail Marzuki (MultiTech Publisher, 2023)
This research was motivated by children's lack of creativity in creating and selecting appropriate learning media for students. Because it is still dominated by Children's Worksheets (LKA). The aim of this research is to describe the use of loose parts media to develop creativity in early childhood as well as supporting and inhibiting factors for the use of loose parts media in the Pembina Waisai State Kindergarten. This research uses qualitative field research methods. The data source was taken from the B1 group of the Pembina Waisai State Kindergarten. Research instruments include observation, interviews and documentation. Meanwhile, the data analysis technique uses Miles and Huberman analysis which consists of data reduction, data presentation and drawing conclusions. The results obtained from this research show that the use of loose parts media in learning plays a role in developing creativity in early childhood by carrying out all stages of using loose parts media using playing strategies, tidying up and storing things as well as various strategies for increasing creativity (product creation, imagination , exploration, and experimentation). In this regard, the supporting factors for the use of loose parts media lie in the role of good teachers and parents as well as the availability of a variety of loose parts media around the school environment and the inhibiting factors lie in children's interests and moods which cannot be conditioned properly.